Study on soil germs capable of mineralizing organic phosphates I.- Introduction and bibliographic review - Barea Navarro, J. M. (Ars Pharmaceutica (Internet), 1969)
We have carried out an introduction of the study and a bibliographic revision of the problem of microbial solubility of P contained in insoluble compounds. The mineralization of organic phosphates has been specially studied.